Elasmobranch diversity with preliminary description of four species from territorial waters of Bangladesh (Bangladesh Journal of Zoology, 2018)
There is a significant lack of data regarding the biodiversity of elasmobranchs in the territorial waters of Bangladesh, since that sharks and rays are not targeted by commercial fishing industry, but rather encountered as a bycatch. This paper updated the diversity of elasmobranchs in the territorial waters of Bangladesh. The study was carried out to identify two coastal areas of Patharghata, Barguna and Cox's Bazar between October, 2015 and September, 2016. Using fish landing station survey techniques, total 20 species of elasmobranch were encountered, including eight species of sharks and 12 species of batoids, under 14 genera, ten families. This is the most expended field based records of elasmobranch fishes of Bangladesh.Bangladesh J. Zool. 46(2): 185-195, 2018